Female Control Of Sexuality: Illusion Or Reality? Use Of Vaginal Products In South West Uganda - Green, Gill; Pool, Robert; Harrison, Susan; Hart, Graham J.; Wilkinson, Joanie; Nyanzi, Stella; Whitworth, James A.G. (Social Science & Medicine, 2001)
This paper reports on a trial of vaginal products that were distributed and used by 131 women and 21 men in south west Uganda. It focuses specifically upon the issue of female control in heterosexual relationships and examines whether methods which are ostensibly under women’s control, will in practice give women greater control of their sexual health. Participants were invited to select two from a range of vaginal products that included the female condom, contraceptive sponge, film, tablets, foam and gel, and use each for five weeks and their favourite product for a further three months. They were interviewed up to seven times over a five-month period. Although the women perceived that a major advantage of the products (with the exception of the female condom) was that they could be used secretly, less than 40% were using the products without their partner’s knowledge after one week and this proportion declined over time with only 22% using the products secretly after ten weeks. In the main male partners were told as women felt it their duty to inform them. In general the women were very much more positive about the products than they were about the male condom, as were the men. A contributory factor to their popularity among women was the greater control they gave them. Even though, use of these products in practice often involved negotiation with male partners, the fact that use was contingent on women’s action was empowering and increased somewhat their ability to control their sexual health.
Keywords: Female control; HIV; Contraceptives; Uganda